2012
DOI: 10.1891/0886-6708.27.4.563
|View full text |Cite
|
Sign up to set email alerts
|

Bystander Perceptions: Implications for University Sexual Assault Prevention Programs

Abstract: The college party environment comprises a risk factor for unwanted sexual activity but may also provide a safety net, given the presence of bystanders who can potentially intervene in risky situations. Sexual assault prevention programs are increasingly incorporating bystander education into their designs. This article presents findings intended to inform these programs. Qualitative data from single-sex focus groups about typical college party behavior was analyzed for common themes. Analysis of these themes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 32 publications
2
51
1
Order By: Relevance
“…Party rape scenarios (see Appendix) were based on descriptions of preassault risk drawn from the literature (e.g., Burn, 2009;Koelsch et al, 2012). Each participant imagined attending a party, either alone or with three friends, where a sober man leads a clearly intoxicated person (either male or female) into a private bedroom.…”
Section: Manipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Party rape scenarios (see Appendix) were based on descriptions of preassault risk drawn from the literature (e.g., Burn, 2009;Koelsch et al, 2012). Each participant imagined attending a party, either alone or with three friends, where a sober man leads a clearly intoxicated person (either male or female) into a private bedroom.…”
Section: Manipulationmentioning
confidence: 99%
“…A common type of preassault situation involves risk for party rape, a type of sexual assault in which an intoxicated person is targeted for sexual access at a social gathering (Armstrong, Hamilton, & Sweeney, 2006). In the preassault stage of a party rape, the drunken partygoer (potential victim) might be escorted to a private room where an incapacitated sexual assault could occur (Burn, 2009;Koelsch, Brown, & Boisen, 2012). To date, men's responses to these types of high-risk situations have not yet been systematically investigated.…”
mentioning
confidence: 99%
“…Specifically, we were most interested in the role of gender and age, rape myth acceptance, and a history of physical and sexual dating aggression victimization, since these are frequently-studied correlates of dating and sexual aggression bystander action among adults (Banyard 2008;Brown et al 2014;Burn 2009;Koelsch et al 2012;McMahon 2010), as well as correlates of dating and sexual aggression perpetration (Basile et al 2013;de Bruijn et al 2006;Reyes andFoshee 2013, Wolitzky-Taylor et al 2008). Furthermore, debunking rape myths is a key component of bystander-focused dating and sexual aggression prevention programming with college students (Eckstein et al 2013;McMahon 2010).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most compelling and overlooked factors is that opportunities to act as a bystander are scarce. Supporting this theory, Flack et al [56] found that 78% of sexual assaults occur within the context of a "hook-up," and a separate study found that "hook-ups" typically take place in relatively isolated or semi-private locations [57]. Given these findings, it is logical to conclude that potential bystanders may lack opportunities to engage in bystander intervention.…”
Section: Community-level Prevention Programsmentioning
confidence: 99%